Angiogenic factors and the risk of preeclampsia: A systematic review and meta-analysis - Yousef Veisani; Ensiyeh Jenabi; Ali Delpisheh; Salman Khazaei (International Journal of Reproductive BioMedicine, 2019)
Background The etiological nature of preeclampsia is heterogeneous. The use of biomarkers indices in early pregnancy helps to have appropriate stratification of pregnancies into high- and low risk for the purpose of choosing timely interventions.